بروفيل شخصية المرأة المجرمة - مزوار, ياسمينة; بركو, مزوز (University of Eloued جامعة الوادي, 2018)
داخل المؤسسة العقابية، حيث حاولت الباحثة الإلمام بكل ما يتعلق بالتراث النظري للدراسة، أما الجانب التطبيقي للدراسة فتم استخدام المنهج الوصفي في شقها الكمي، والمنهج الإكلينيكي في شقها الكيفي حيث استخدم في الدراسة الكمية استبيان المظاهر المرضية لاضطرابات الشخصية على عينة مكونة من 22 سجينة موزعة على مؤسستين عقابيتين، أما الدراسة الكيفية فاستُخدمت فيها آداتين من أدوات جمع البيانات وهي المقابلة واختبار الرورشاخ على عينة مكونة من أربعة نسوة. توصلت الدراسة إلى أن المرأة المجرمة تتميز ببروفيل شخصية مرضية تعاني اضطراب الشخصية السيكوباتية، كما تتميز بسمات وخصائص نفسية كالعدوانية، القلق والإكتئاب، وخلصت الدراسة إلى أن البناء النفسي المضطرب للمرأة يساهم في ولوجها لعالم الجريمة. Abstract : The purpose of this study was to know the psychological profile of criminal women and to put them within the penal institution, where the researcher tried to know all about the theoretical heritage of the study. The practical side of the study was the descriptive approach in its quantification and the clinical approach in its qualitative section. The pathological manifestations of personality disorders on a sample of 22 prisoners were divided into two penal institutions. The qualitative study used two data collection tools, namely, the interview and the Rorschach test on a sample of four women. The study found that the criminal woman is characterized by a personality character suffering from personality disorder, and also characterized by characteristics and psychological characteristics such as aggression, anxiety and depression, and concluded that the troubled psychological construction of women contributes to the world of crime.
Profile of the criminal woman
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 04 جامعة الوادي
Keywords: المرأة، البروفيل، البروفيل النفسي، الاجرام، الجريمة، المرأة المجرمة، السجن; Women, profile, psychological profile, world of crime, crime, criminal women, prison